Clinical Characteristics and the Risk Factors of Hepatic Injury in 221 Children With Infectious Mononucleosis - Zhang, Chao; Cui, Shu; Mao, Guoshun; Li, Guitao (Frontiers in Pediatrics, 2022)
Background: Infectious mononucleosis caused by Epstein-Barr Virus infection is a common acute infectious disease in children. About 40%-80% of children with infectious mononucleosis have hepatic injury, and hepatic failure is one of the main causes of death in patients with fatal infectious mononucleosis. Identifying the demographics, presenting clinical characteristics and the risk factors of hepatic injury in infectious mononucleosis children are helpful to remind clinicians which patients are prone to have hepatic damage. Methods: A descriptive, cross-sectional study with a 31-month retrospective review was performed on all infectious mononucleosis children hospitalized in the pediatric department of Fuyang People's Hospital. Demographic data, presenting features, radiology imaging, clinical and laboratory parameters, and clinical outcomes of infectious mononucleosis children were collected. Results: Two-hundred twenty-one infectious mononucleosis inpatients were enrolled, and 43.9% (97/221) patients were considered to have a hepatic injury (defined as alanine amino transaminase >40 U/L). Compared with patients without hepatic injury, hepatic injury patients were marked with a significantly higher percentage of hepatomegaly (31% versus 49%), splenomegaly(58% versus 81%) and palpebral edema (47% versus 63%), higher age (3.05 ± 2.12 versus 3.84 ± 2.44), hospitalization days (6.85 ± 2.64 versus 8.08±2.83), leukocyte (14.24 ± 5.32 versus 18.53±8.63), lymphocytes (9.48 ± 4.49 versus 13.80 ± 7.47), the proportion of atypical lymphocytes (0.12 ± 0.07 versus 0.15 ± 0.08) and aspartate aminotransferase (33.71 ± 10.94 versus 107.82 ± 93.52). The results of correlation analysis and multiple linear regression analysis indicated that age (OR=1.185; 95% CI=1.035-1.357, p=0.014), female (OR=2.002, 95% CI: 0.261-0.955, p = 0.036) and splenomegaly (OR=2.171, 95% CI: 1.018-4.628, p = 0.045) were independent risk factors of hepatic injury. Conclusions: In this study, the hepatic injury was associated with gender, age, and splenomegaly, which improved our understanding of risk factors about hepatic injury among infectious mononucleosis children.